2017
DOI: 10.1016/j.physc.2016.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Visualised predictions of gap anisotropy to test new electron pairing scheme

Abstract: The rich and fertile but not yet adequately exploited ground of superconductor anisotropy is proposed as a test bed for a new empirical scheme of electron pairing. The scheme is directed to resolving a numerical and conceptual difficulty in the BCS theory. The original theoretical formulation of the anisotropy problem by Bennett is adopted and its outcomes extensively explored. Here the Bennett conclusion that in metallic superconductors phonon anisotropy is the principal source of gap anisotropy is accepted. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…For some time we have been investigating why it has been so difficult to find consistent values of ρ(T) and α 2 F(ν) [5][6][7][8][9][10][11][12][13][14] and confirmed that the strength of the interactions has been overestimated in the superconducting state [7]. Starting from experimental values of ρ(T), we found from inversion the effective Coulomb potential, or pseudopotential, that determines the values of the matrix element in the normal state.…”
Section: Introductionmentioning
confidence: 75%
See 4 more Smart Citations
“…For some time we have been investigating why it has been so difficult to find consistent values of ρ(T) and α 2 F(ν) [5][6][7][8][9][10][11][12][13][14] and confirmed that the strength of the interactions has been overestimated in the superconducting state [7]. Starting from experimental values of ρ(T), we found from inversion the effective Coulomb potential, or pseudopotential, that determines the values of the matrix element in the normal state.…”
Section: Introductionmentioning
confidence: 75%
“…In short, we have calibrated values of the matrix element, g ℓ (ν) in equation (13), for the electron-phonon interactions. We understand that, when a metal is in the normal state, these interactions manifest themselves as electrical resistivity.…”
Section: Electrical Resistivity: Leadmentioning
confidence: 99%
See 3 more Smart Citations